An experimental and numerical study on the combustion and flame characteristics of hydrogen in intersecting slot burners. (1st February 2018) - Kiani, Mehrdad; Houshfar, Ehsan; Ashjaee, Mehdi
Abstract: In the present study, two impinging slot jets of hydrogen gas at different angles and distances are investigated experimentally using the Mach-Zehnder interferometry. The obtained temperatures from the interferometry method were validated against the thermocouple measurements. The generated temperature field is studied using infinite fringe interferometry. Slot burners with high length-to-width ratio are utilized to ensure producing a uniform 2D flow. The slot burners' angle and the distance between the burners are varied from 60 to 100° and 10 mm–25 mm in the increment of 20° and 5 mm, respectively. The Reynolds number is varied from 70 to 150, and the equivalence ratio is changed from 0.8 to 2.5. The results indicated that the Reynolds number does not have a considerable effect on increasing the maximum temperature, while, it has a significant influence on the flame structure. The equivalence ratio has a substantial effect on both maximum temperature and flame structure. Also, the variations in angle of burners have a considerable effect on the flame stability. Furthermore, the distance of burners strongly affects the maximum flame temperature and the flame structure. It was observed that by increasing the burners distance, the domain of maximum temperature is descended. The results from numerical modeling were also validated with experiments. The effect of temperature on the NO x emissions was clearly shown in the CFD simulations. Highlights: Effect of operating conditions was determined for two impinging flames of hydrogen. The temperatures of flames were measured numerically and experimentally by MZI. Maximum flame temperature increases slightly with Reynolds number. Distance of burners has a strong effect on the flame temperature and configuration.